Formation of efficiency factors in the use of intellectual property - Maslak, M. V. (Вінницький національний технічний університет, 2023)
A study of methodical approaches to determining the effectiveness of the use of intellectual property at enterprises was conducted. The matrix of the formation of external and internal factors of influence on the performance indicators of intellectual property objects at enterprises is proposed.
Формування факторів ефективності використання об’єктів інтелектуальної власності
Keywords: intellectual property objects; economic efficiency; matrix of factors